A Comparison of Aggregatibacter actinomycetemcomitans (Aa) Virulence Traits in a Rat Model for Periodontal Disease - Schreiner, Helen (Public Library of Science, 2013)
Our aim was to explore the effects of Cytolethal Distending toxin (Cdt) in a well established rat model of periodontal disease where leukotoxin (LtxA) was thought to have no known effect. In vitro studies, were used to assess CdtB activity using Aa Leukotoxin as a negative control. These studies showed that both CdtB and LtxA (unexpectedly) exerted significant effects on CD4(+) T cells. As a result we decided to compare the effects of these two prominent Aa virulence factors on bone loss using our rat model of Aa-induced periodontitis. In this model, Aa strains, mutant in cdtB and ltxA, were compared to their parent non-mutant strains and evaluated for colonization, antibody response to Aa, bone loss and disease. We found that bone loss/disease caused by the ltxA mutant strain, in which cdtB was expressed, was significantly less (p<0.05) than that due to the wild type strain. On the other hand, the disease caused by cdtB mutant strain, in which ltxA was expressed, was not significantly different from the wild type strain. This data indicates that Aa LtxA exerts a greater effect on bone loss than Cdt in this rat model of periodontal disease and supports the utility of this model to dissect specific virulence factors as they relate to immunopathology in studies of Aa-induced disease.